Identity construction on Facebook among young Malaysians / Tan Jenny - Tan, Jenny (2014)
The advancement of technology allows people to communicate globally without barriers and thus, increases the usage of Computer-Mediated-Communication (CMC). One example of CMC is the social networking site. Social networking sites are popular and they continue to grow due to the large number of users. Many studies have been conducted to explore identity construction on the Internet and it was found that many users are publishing favourable images and information of themselves in order to maintain an ideal self among their audience. The purpose of this research is to examine how young Malaysians construct multiple identities and portray themselves in a self-preferred image projection via status updates on their Facebook profiles through the use of different linguistic, semiotic and visual features. This research wants to explore the range of identity claims people use in a non-anonymous online setting. The participants of this research comprised of ten males and ten females from the age group of 24 to 28. All participants are Malaysian citizens and are currently residing in Kuala Lumpur, a metropolitan city in Malaysia. This research is a qualitative research which uses the case study strategy in order to study a group of individuals based on data collected over a period of one month. The sampling methods used in this research are convenience sampling and homogenous sampling. Findings show that participants frequently use Facebook to keep in touch and to share thoughts with their audiences. Though gender identity is not intended for this research, it is found that male participants and female participants post significantly different topics of interest. Female participants show greater interest in friendship/relationship matters while male participants show greater interest in work-related or political issues. Most participants emphasise that they post whatever issues they wish to on Facebook and they are not concerned with how others view them but stress that they are cautious in their posts in order to avoid being offensive and to prevent misunderstanding. In short, identity construction does occur among these young Malaysians. The research shows that the participants want to portray a positive image. Though no exact identity is identified, self-presentation is clearly reflected in the topics discussed and the writing strategies used by these participants.